Ligand-dependent Hedgehog pathway activation in Rhabdomyosarcoma: the oncogenic role of the ligands - Almazán-Moga, Ana; Simon-Keller, Katja (British journal of cancer, 2017)
Background: Rhabdomyosarcoma (RMS) is the most common type of soft tissue sarcoma in children. The Hedgehog (HH) pathway is known to develop an oncogenic role in RMS. However, the molecular mechanism that drives activation of the pathway in RMS is not well understood. Methods: The expression of HH ligands was studied by qPCR, western blot and immunohistochemistry. Functional and animal model studies were carried out with cells transduced with shRNAs against HH ligands or treated with HH-specific inhibitors (Vismodegib and MEDI-5304). Finally, the molecular characterisation of an off-target effect of Vismodegib was also made. Results: The results showed a prominent expression of HH ligands supporting an autocrine ligand-dependent activation of the pathway. A comparison of pharmacologic Smoothened inhibition (Vismodegib) and HH ligand blocking (MEDI-5304) is also provided. Interestingly, a first description of pernicious off-target effect of Vismodegib is also reported. Conclusions: The clarification of the HH pathway activation mechanism in RMS opens a door for targeted therapies against HH ligands as a possible alternative in the future development of better treatment protocols. Moreover, the description of a pernicious off-target effect of Vismodegib, via unfolded protein response activation, may mechanistically explain its previously reported inefficiency in several ligand-dependent cancers.
Gesehen am 15.08.2018